Free speech - Haworth, Alan, 1944- (Problems of philosophy (Routledge (Firm)), 2002)
Free Speech is a philosophical treatment of a topic which is of immense importance to all of us. Writing with great clarity, wit, and genuine concern, Alan Haworth situates the main arguments for free speech by tracing their relationship to contemporary debates in politics and political philosophy, and their historical roots to earlier controversies over religious toleration. Free Speech will appeal to anyone with an interest in philosophy, politics and current affairs.